Analisis Kandungan Formalin dalam Bumbu Giling Instan di Pasar Besar Kota Malang - Fendi Yoga Wardana; Arnis Riawati; Beta Herilla Sekti (PROFESSIONAL HEALTH JOURNAL, 2023)
Ground spices are food ingredients that can enrich the taste, aroma and taste of dishes and have a very limited service life. Many manufacturers use formalin as a preservative to overcome the short shelf life of ground spices. Formalin is a clear, colorless or almost colorless liquid with a pungent odor. The use of formalin as a food preservative is prohibited in the Regulation, because formaldehyde is toxic (poisonous). This study identified the formalin content in instant ground spices in the market of Malang City. The purpose of this study was to determine the content and levels of formaldehyde contained in five traders of instant ground spices in Market of Malang City. Five samples of instant ground spices that were analyzed were taken using the Purposive Sampling technique. Qualitative testing was carried out using the Test Kit and quantitative testing for the determination of formalin levels was carried out using the Spectrophotometry UV-VIS . The results showed that based on observations and qualitative tests, two samples of instant ground spices sold in Market were positive for formaldehyde. Meanwhile, the quantitative test results using the Spectrophotometry UV-Vis showed that of the five samples tested, two of them contained 0.378% formalin in Rendang instant ground spice and 0.516% instant curry spice. So the curry and rendang samples are not suitable for consumption because formaldehyde cannot be added to food at all.